Failure analysis of naval vessel's mooring system and suggestion of reducing mooring line tension under ocean wave excitation. (November 2015) - Lee, Kyoung-Hyun; Han, Hyung-Suk; Park, Sungho
Abstract: A moored ship can experience problems when subjected to heavy environmental loads. In most cases, wind and current loads are the only design considerations for the mooring situation in the harbor, and wave loads are not considered due to the low wave amplitudes in harbors. However, many new harbors are constructed near the open sea, and entrance channels are being built deeper and wider than the classical harbors. So, many cases of mooring failure due to heavy wave loads are recently being reported in harbors. In this paper, failure analysis has been performed on a ship in harbor with mooring failure. The failure analysis results demonstrated that the wave drift forces can cause failure of the mooring system. Therefore, consideration for new design of mooring system, which considers the wave loads, is suggested. Highlights: Failure analysis of the fracture of a Mooring system of naval vessel was performed Fracture was studied by calculating the vessel motion under the wave excitation and structural analysis. It can be found that main contributor of the failure is the wave drift force Dynamic force can be reduced by changing the dipping method of the mooring line.